PROTOTYPE ALAT PENDETEKSI GAS BERBAHAYA DI KAMAR MESIN UNTUK MENJAGA KESELAMATAN ABK BERBASIS WEMOS D1 DI KAPAL MT PLAJU - Purnama Dewi, Nanda; Nasri, Nasri; Purwanto, Sigit; Retno Gunarti, Monika; Dai Robbi, Shofa (Penerbit Lafadz Jaya, 2025)
Enclosed spaces in ship engine rooms pose significant risks due to toxic gas accumulation like carbon monoxide and carbon dioxide, contributing to maritime fatalities. This research aimed to develop a Wemos D1-based prototype for real-time hazardous gas detection to enhance crew safety on MT Plaju tanker. Experimental prototype development employed ADDIE model with static and dynamic testing on MQ-135 sensor, buzzer, LED, and WiFi web monitoring. Population comprised four main holes (A-D) in engine room enclosed spaces, sampled through 20 measurements during 12-month sea practice. Instruments included Arduino IDE for programming and Excel for regression linear analysis with <5% calibration error. Results showed average CO detection at 5.4 ppm and CO2 at 406 ppm, with alarm response under 6 seconds exceeding 30% threshold, achieving 95% accuracy in high humidity and vibration conditions. The prototype demonstrated superior WiFi connectivity over previous ATMega328P systems, reducing hazard zones by 40%. In conclusion, this cost-effective IoT solution validates hardware reliability for Indonesian maritime operations, recommending multi-gas sensor integration for industrial scaling.